A magia do ponto riscado na Umbanda esotérica - Solera, Osvaldo Olavo Ortiz (2015)
Umbanda is known for being a genuinely Brazilian religion, but its origin is still controversial and subject to discussion. The richness and diversity of ritualization and understanding of the Sacred has arised the curiosity of scholars and academics. In such a milieu, the scratched signs on the magic of Esoteric Umbanda constitute yet an understudied topic. Thus, this research is based on the scratched signs that are nominated by their followers as Pemba Signal. The comparative study of scratched signs resulted a correlation with the three forming matrices of the Brazilian people: the Indo-European, the Indian and the African. In this study, we noticed that the scratched signs have elements that establish a hierarchy and determine and identify the spiritual entity that is evoked to work in public attendances of Umbanda Esoteric. By using these signals, the followers of Esoteric Umbanda revive them and therefore give continuity to the myths that contain such signs, sometimes Indian, sometimes African, sometimes Indo-European. In tracing such signals, followers / initiated establish the sacred space where such signs and entities will act as well as the collective heritage evoked that make up the structure of theirs consciousness. It may be noted that the Brazilian man is unique because he carries inside himself and in his religiosity the ancestral element of the matrices which constitute his conscience